Acupuncture therapies for relieving pain in pelvic inflammatory disease: A systematic review and meta-analysis. - Lichen Yi; Baoyi Huang; Yunyun Liu; Luolin Zhou; Yingjie Wu; Chengyang Yu; Wenjie Long; Yuemei Li (PLoS ONE)
Background Studies investigating the effectiveness of acupuncture therapies in alleviating pain in pelvic inflammatory disease (PID) have gained increasing attention. However, to date, there have been no systematic reviews and meta-analyses providing high-quality evidence regarding the efficacy and safety of acupuncture therapies in this context. Objective The objective of this review was to assess the efficacy and safety of acupuncture therapies as complementary or alternative treatments for pain relief in patients with PID. Method A comprehensive search was conducted in eight databases from inception to February 20, 2023: PubMed, Embase, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, Wanfang Database, VIP Database, and Chinese Biomedical Literature Database. Randomized controlled trials (RCTs) investigating acupuncture therapies as complementary or additional treatments to routine care were identified. Primary outcomes were pain intensity scores for abdominal or lumbosacral pain. The Cochrane risk of bias criteria was applied to assess the methodological quality of the included trials. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) system was used to evaluate the quality of evidence. Data processing was performed using RevMan 5.4. Result This systematic review included twelve trials comprising a total of 1,165 patients. Among these, nine trials examined acupuncture therapies as adjunctive therapy, while the remaining three did not. Meta-analyses demonstrated that acupuncture therapies, whether used alone or in combination with routine treatment, exhibited greater efficacy in relieving abdominal pain compared to routine treatment alone immediately after the intervention (MD: -1.32; 95% CI: -1.60 to -1.05; P < 0.00001). The advantage of acupuncture therapies alone persisted for up to one month after the treatment (MD: -1.44; 95% CI: -2.15 to -0.72; P < 0.0001). Additionally, acupuncture therapies combined with routine treatment had a more pronounced effect in relieving lumbosacral pain after the intervention (MD: -1.14; 95% CI: -2.12 to -0.17; P < 0.00001) in patients with PID. The incidence of adverse events did not increase with the addition of acupuncture therapies (OR: 0.56; 95% CI: 0.21 to 1.51; P = 0.25). The findings also indicated that acupuncture therapies, as a complementary treatment, could induce anti-inflammatory cytokines, reduce pro-inflammatory cytokines, alleviate anxiety, and improve the quality of life in patients with PID. Conclusion Our findings suggest that acupuncture therapies may effectively reduce pain intensity in the abdomen and lumbosacral region as complementary or alternative treatments, induce anti-inflammatory cytokines, decrease pro-inflammatory cytokines, alleviate anxiety, and enhance the quality of life in patients with PID, without increasing the occurrence of adverse events. However, due to the low quality of the included trials, the conclusion should be interpreted with caution, highlighting the need for further high-quality trials to establish more reliable conclusions.